1985
DOI: 10.1083/jcb.101.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Location of a fibronectin domain involved in newt epidermal cell migration.

Abstract: The interaction of migrating newt epidermal cells with the extracellular matrix protein, fibronectin, was studied. Pieces of nitrocellulose coated with intact human plasma fibronectin or proteolytically derived fragments were implanted into wounded limbs so that the coated nitrocellulose served as wound bed for migrating epidermal cells as they attempted to form a wound epithelium. Epidermal cells migrated very poorly on nitrocellulose pieces coated with (a) a 27-kD amino-terminal heparin-binding fragment, (b)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 32 publications
(23 reference statements)
1
11
0
Order By: Relevance
“…Previous reports confirmed that the amino-terminal 27-kDa tryptic fragment bound specifically to S. aureus in suspension [15] or after adsorption on surfaces [16,41]. We also found a significant adherence-promoting activity in a mixture of 190-and 200-kDa tryptic fragments lacking both the amino-and carboxy-terminal ends of fibronectin [27,28]. The mixture of 190-and 200-kDa fragments adsorbed on gelatin-precoated cannula segments in parallel with intact fibronectin promoted S. aureus Cowan I adherence at equivalent amounts of adsorbed protein, although to a slightly lower extent (figure 4B).…”
Section: Selective Inactivation Ofadherence-promoting Activity Offibrsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous reports confirmed that the amino-terminal 27-kDa tryptic fragment bound specifically to S. aureus in suspension [15] or after adsorption on surfaces [16,41]. We also found a significant adherence-promoting activity in a mixture of 190-and 200-kDa tryptic fragments lacking both the amino-and carboxy-terminal ends of fibronectin [27,28]. The mixture of 190-and 200-kDa fragments adsorbed on gelatin-precoated cannula segments in parallel with intact fibronectin promoted S. aureus Cowan I adherence at equivalent amounts of adsorbed protein, although to a slightly lower extent (figure 4B).…”
Section: Selective Inactivation Ofadherence-promoting Activity Offibrsupporting
confidence: 90%
“…aureus-binding domain [15,26] and previously referred to as the 180-kDa carboxy-terminal fragment [15], was prepared by trypsin digestion as previously described in detail [15]. These fragments, appearing as two closely spaced bands on SDS-PAGE (190 and 200 kDa), have subsequently been shown to be produced from the A and B chains, respectively [27], and to contain the collagen, heparin, and cell-binding regions, but not the carboxy-terminal end including the disulfide bonds connecting both subunits of fibronectin [27,28]. The mixture of 190-and 200-kDa fragments was purified from the 27-kDa fragment by chromatography on DEAE-Sepharose.…”
Section: Preparation Of Purified Fibrinogen and Fibronectin Fragmentsmentioning
confidence: 99%
“…A later study by Donaldson et al . attempted to localise the domain of fibronectin that mediates this migration. They demonstrated that new epidermal cell migration is restricted to a domain in the middle third of the gene.…”
Section: Role Of Fibronectin In Ecm Formation In the Proliferative Phmentioning
confidence: 99%
“…In urodeles, the initial response to the injury is the formation of a fibrin clot that covers the wound surface and provides a substrate on which peripheral epidermal cells migrate to close the wound (Donaldson et al, 1985(Donaldson et al, , 1987. This process is initiated by cells at the wound edge extending lamellipodia and actively moving across the wound, and more proximal cells similarly extending lamellipodia behind these lead cells (Mahan and Donaldson, 1986;Dungan et al, 2002).…”
Section: Wound Healing and Dedifferentiationmentioning
confidence: 99%